Asthma Care Quality Measures at Children's Hospitals and Asthma-Related Outcomes. Issue 4 (July 2016) - Subramony, Anupama; Hall, Matthew; Thomas, Cherie; Chiang, Vincent W.; McClead, Richard E.; Macias, Charles G.; Frank, Gary; Simon, Harold K.; Mann, Keith; Morse, Rustin
Abstract: Objective: The Joint Commission requires hospitals to report on Children's Asthma Care (CAC) measures, although their relationship to outcomes is not clear. The objective of this study was to (1) characterize metrics hospitals use for asthma, and to (2) determine if the number and type of metrics used is associated with readmission rates. Study Design: Pediatric hospital quality leaders were asked to identify asthma metrics utilized by their respective organizations via an online survey. "Use" of metrics was defined as periodically measuring data regardless of performance. Linear regression was used to determine if the number or domain of metrics grouped by topic used was associated with 7-, 30-, and 90-day same-cause readmission rates obtained from the Pediatric Health Information System (PHIS). Results: Among respondents ( n = 27, 62.7%), the mean number of metrics used was 20.5 ( SD = 9.1, range = 4–38). There was no association between the number or domain type of metrics used and 7-, 30-, or 90-day readmission rates. Conclusions: Despite using a wide variety of asthma metrics, there was no association between use of any metric or domain of metrics and asthma-related readmission rates. Additional work should identify asthma process measures that are associated with meaningful outcomes.